Use of dried urine spots for screening of inborn errors of bile acid synthesis. Issue 5 (15th May 2019) - Naritaka, Nakayuki; Suzuki, Mitsuyoshi; Takei, Hajime; Chen, Huey‐Ling; Oh, Seek‐hi; Kaewplang, Pinyada; Zhang, Chunhua; Murai, Tsuyoshi; Kurosawa, Takao; Kimura, Akihiko; Shimizu, Toshiaki; Nittono, Hiroshi
Abstract: Background: In pediatric patients with cholestasis of unknown cause, inborn errors of bile acid (BA) synthesis (IEBAS) may be considered. For the initial screening for IEBAS, clarification of the urine BA profile is essential. The transportation of urine in a frozen state via air delivery, however, is laborious and costly. This study assessed the feasibility of using dried urine spots (DUS) to establish a more convenient and affordable method of IEBAS screening. Methods: We created DUS using urine samples from patients with 3β‐hydroxy‐Δ5‐C27‐steroid dehydrogenase/isomerase deficiency (3β‐HSD) and Δ4‐3‐oxo‐steroid 5β‐reductase deficiency as standard preparations. We started accepting DUS specimens by regular mail. Results: The ratio of unusual to usual BA is essential for the initial detection of IEBAS, and the recovery rates of abnormal BA were acceptable. The recovery rate of Δ4‐BA on day 28 decreased to 31.8% at 25°C, and to 19.6% at 37°C. Therefore, the sending of DUS should be avoided under conditions of high temperature. Of a total of 49 children with cholestasis, eight new patients were diagnosed with IEBAS using this screening method. Conclusion: The mailing screening system is expected to facilitate the shipment, from regions outside of Japan, of samples for IEBAS screening.